Polityczne i ekonomiczne problemy rozwoju strefy euro (Politeja, 2020)
Political and Economic Problems of the Euro Area DevelopmentThe aim of the article is to examine how political and economic changes introduced in the field of economic governance as a result of the economic crisis will affect the effectiveness of economic policy at the supranational level. The first part presents problems related to the political conditions of the functioning of the euro area. In the second part, proposals for institutional changes affecting the improvement of economic policy coordination were analysed. The research was based on the theory of the optimal currency area using the system method.